2021
DOI: 10.3389/fphar.2021.656697
|View full text |Cite
|
Sign up to set email alerts
|

Falcarindiol Enhances Cisplatin Chemosensitivity of Hepatocellular Carcinoma via Down-Regulating the STAT3-Modulated PTTG1 Pathway

Abstract: Hepatocellular carcinoma (HCC) is the most frequent primary liver malignancy globally and the third leading cause of cancer-related death. Chemotherapy is one of the main methods in treating HCC, while recent studies have found that the resistance of HCC to chemotherapeutic drugs reduces the efficacy of the chemotherapy. Falcarindiol (FAD) is a cytotoxic and anti-inflammatory polyacetylenic oxylipin found in food plants of the carrot family (Apiaceae), while its role in HCC remains to be explored. Here, HCC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In addition, the JAK/STAT and MAPK signalling pathways are associated with antitumour immunity 59 . Both the JAK/STAT and MAPK pathways have been confirmed to be crucial targets in related studies of HCC resistance 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the JAK/STAT and MAPK signalling pathways are associated with antitumour immunity 59 . Both the JAK/STAT and MAPK pathways have been confirmed to be crucial targets in related studies of HCC resistance 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…FAD led to cell death through the induction of apoptosis, autophagy and endoplasmic reticulum stress. It is important to note that FAD did not interfere with cisplatin e ciency, and interestingly had synergistic effects in combination with cisplatin to suppress HCC cells (Hong et al, 2021). These results emphasize on the anti-cancer potential of FAD in addition to its anti-in ammatory and antioxidant capabilities; Nevertheless, the effects of FAD treatment on normal stem cells have not been fully evaluated yet; for example, one study exhibited deleterious effects for FAD on the neural stem cells in which impairs the balance between self-renewal and differentiation status (Kim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Moreover, it has also been demonstrated that securin played a critical role in facilitating EMT, invasion, metastasis, and chemoresistance of HCC cells. [ 76 , 77 ] In colorectal cancer, securin can lead to genetic instability by inhibiting Ku70 activity and disturbing the nonhomologous end-joining dsDNA repair pathway. [ 16 ] In addition, accumulated evidence has shown that securin represses drug-induced senescence and apoptosis [ 26 , 63 , 78 , 79 ] and contributes to the migration and invasion of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%